(untitled) (Entrepreneurship Journal for Finance and Business, 2025)
The current study aims to identify the most important dimensions of customer emotional compatibility with digital and electronic products of organizations and their role in customer persuasion engineering, given that current or future organizations are digital organizations capable of manipulating the thoughts, visions, minds, and values ​​of customers and directing them toward their products. This indicates that the next sustainable development is digital sustainable development, as the digital transformation has cast its shadow over all organizations today. How will this be in the future after the rapid development of digital sciences? Therefore, our study consisted of two variables: the independent variable, emotional compatibility, which consists of a set of dimensions (emotional promotion, customer behavior modification, customer need awareness, customer partnership), and the dependent variable, customer persuasion engineering, which also includes a set of sub-dimensions (traditional customer persuasion engineering, revealed preference engineering, collective neurological customer persuasion engineering, and mind-gaming engineering). The digital sustainability variable was a one-dimensional variable. The importance of the study, which focused on the topic of customer persuasion engineering, a modern marketing topic, as well as customer emotional compatibility, and how organizations can create an aura of influence between the emotional compatibility processes between the customer and the product to be purchased. In other words, when emotional compatibility exists, it is possible to facilitate the customer persuasion engineering process, which is what most digital organizations seek today. The study sample consisted of (158) digital product customers. The study reached the most important conclusion: the more digital organizations are able to identify the dimensions influencing emotional compatibility, the easier it will be to implement customer persuasion engineering. The study also recommends that all marketing organizations use and enhance emotional compatibility methods and techniques to facilitate customer persuasion engineering and create sustainable digital development.